Finite element based fatique analysis of aluminium tailor welded blanks - Che Azral Izzuddin, Che Rudi (2013)
This project describes finite element based fatigue analysis of aluminium tailor welded blanks. Since the title stated aluminium, for analysis four type of aluminium were used. The selected aluminium types were aluminium 5083-O, aluminium 5182-O, aluminium 6063-T6 and aluminium 7075-0. The structure of specimen was modeled using Solidwork software. Finite element modeling and linear analysis performed using MSC.PATRAN and MSC NASTRAN. Fatigue life prediction was carried out by using MSC FATIGUE. Linear static analysis was carried out to obtained stress/strain state result. The mesh convergence analysis performed to select best mesh for analysis. Stress life method and strain life method was used for comparison of fatigue life with different type of loading such as SAETRN, SAESUS and SAEBKT also applied during analysis. From analysis, rectangular specimen used straight weld with combination of aluminium 6063-T6 with aluminium 5083-O produced the highest maximum principical stress. Goodman method produced better fatigue distribution for stress life method and for strain life method is SWT method.